Rancang Bangun Sistem Informasi Untuk Pencatatan Akuntansi Untuk Pembelian ATK Berbasis WEB Dengan Laravel 7.0 - Sundari Utami, Shinta; Elin Panca Saputra, panca; Armaniah, Henny; Priyono, Priyono; Thaka, Indra (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
Abstract - Information technology is a tool used to transform data into meaningful information and facilitate a more productive, efficient and simple workforce. How is the development of this accounting information system in terms of information quality, internal control and daily accounting operations? What is still recorded in the books are errors in accounting calculations and stationery purchases. Using the Microsoft Excel program to help with assignments often causes various problems. Additionally, Laravel seeks to improve software quality by lowering development, startup, and maintenance costs, as well as user experience in using applications. to offer expressive, simple, and efficient syntax. The following are several approaches that the author uses, namely direct observation (Observation). This technique is used to search for and collect information that will be used in processing accounting data. Next, a literature review where the author collects the data and information needed to complete the assignment. Lastly, through consulting academic sources and books. Conclusion The conclusions of this research include making data processing easier from a system that was originally manual but has now switched to being more automatic, increasing accuracy and reducing data collection errors, fast procedures, and more effective business transactions.